Rates of vascular access use in transcatheter aortic valve replacement: A look into the next generation. Issue 4 (10th August 2015) - Basir, Mir Babar; Velez, Carlos; Fuller, Brittany; Wyman, Janet; Paone, Gaetano; Wang, Dee Dee; Guerrero, Mayra; Greenbaum, Adam; O'Neill, William
Abstract : Objective/Background: As smaller TAVR delivery systems emerge we sought to identify differences in vascular access use. Methods: We analyzed all patients who had undergone TAVR in a single‐center from March 2012 to May 2014. We identified all patients who had undergone nonfemoral TAVR and reviewed their femoral dimensions using CT imaging taking into vascular pathology and minimal lumen diameter (MLD). We then identified those patients in whom a smaller delivery system could have been used if such technology was available at that time. Results: In total 208 consecutive TAVRs were performed, 129 cases using femoral arterial access and 75 cases using non‐femoral access; 28 transapical, 27 transcaval, 12 transaortic, and 8 via an antegrade transseptal venous approach. Of the 75 nonfemoral access cases, 63 were completed using commercially available first‐generation valves (Sapien Valve) and 12 using second‐generation valves under research protocols (Sapien XT Valve). Of the 63 cases performed via a non‐femoral route using a first generation valve, 31 cases could have been approached via a transfemoral (TF) route using second‐generation delivery systems; and 48 cases could have been approached via a TF route using third generation delivery systems (S3 Valve). Of the 12 cases performed via a nonfemoral route using a second‐generation valve, 4 cases could have been approached via a TF route using a third‐generation delivery system. In total, only 11% of patients undergoing TAVR could not accommodate smaller second and third generation devices. Conclusions: As second and third generation devices become commercially available, we anticipate that 89% of cases will be preformed using a TF approach. © 2015 Wiley Periodicals, Inc.